Theories of inflation - Frisch, Helmut (Cambridge [Cambridgeshire] ; New York : Cambridge University Press, 1983)
A survey of the new theories of inflation that have developed over the past two decades in response to the inflationary pressures experienced by Western countries. It examines the shifting debate from explaining inflation as a "causal" process to explaining its increase as a result of constantly changing expectations.
Based on: Die neue Inflationstheorie. Göttingen : Vandenhoeck und Ruprecht, 1980.
Includes bibliographical references (p. 250-258) and indexes.
lje 02/04/13
Loan
Keywords: Inflation (Finance); Inflation - theories